DOI: 10.31274/etd-180810-2278
|View full text |Cite
|
Sign up to set email alerts
|

guided-inquiry based laboratory instruction: investigation of critical thinking skills, problem solving skills, and implementing student roles in chemistry

Abstract: The Chemistry Laboratory: Overview of the Three Courses in the Study…………………………………………………………………... Study Participants……………………………………………………. Data Collection………………………………………………………………... Data Analysis………………………………………………………………….. vi Hoyo Rubric…………………………………………………………... York Technical College (YTC) Rubric……………………………… Results and Discussion……………………………………………………….. Distribution(s) for Groups in the Study…………………………….. Baseline Comparison for 177L, 167L, 401L for Scores on First Laboratory Activity…………………………………………………... Dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
(72 reference statements)
2
9
0
2
Order By: Relevance
“…This finding is consistent with those of Fostveldt et al (2012) and Gupta (2012) who, in separate studies, found that students using the SWH approach had significantly better critical thinking scores than their counterparts in TRAD streams. This finding is consistent with those of Fostveldt et al (2012) and Gupta (2012) who, in separate studies, found that students using the SWH approach had significantly better critical thinking scores than their counterparts in TRAD streams.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with those of Fostveldt et al (2012) and Gupta (2012) who, in separate studies, found that students using the SWH approach had significantly better critical thinking scores than their counterparts in TRAD streams. This finding is consistent with those of Fostveldt et al (2012) and Gupta (2012) who, in separate studies, found that students using the SWH approach had significantly better critical thinking scores than their counterparts in TRAD streams.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with results obtained by Gupta (2012) and Solon (2007), who both reported modest gains in critical thinking for students in traditional classes, and suggest that gains in critical thinking can occur even in the absence of deliberate interventions. This finding is consistent with results obtained by Gupta (2012) and Solon (2007), who both reported modest gains in critical thinking for students in traditional classes, and suggest that gains in critical thinking can occur even in the absence of deliberate interventions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous reports indicate that Biomedical Engineering junior students who participated in one inquiry-based physiology laboratory outperformed classmates who engaged in a conventional laboratory experience on exam questions dealing with the topic explored in the laboratory [1] . Likewise, students involved in inquiry-based laboratories in a first-year general chemistry courses obtained higher scores on standard course exams and on laboratory practical exams compared to matched students engaged in traditional follow-the-steps laboratories [2] . They also prepared higher-quality laboratory reports when compared to the students who had the conventional laboratory experience.…”
Section: Contrast With Follow-the-stepsmentioning
confidence: 92%
“…When questioned about the instructions, students are often incapable of explaining why the instructions asked them to proceed in a certain way rather than in a different way. In addition, the traditional approach does not promote creativity in the laboratory since students are told what to do in exact detail [2] .…”
Section: Introductionmentioning
confidence: 99%